The Influence of Urban Design on Relative Humidity: A Microclimatic Simulation Study in Niterói, Brazil - Santos, Steffany Martins dos; Freitas, Gabriel Souza; Lomardo, Louise Land Bittencourt (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – To evaluate the influence of different urban configurations on relative humidity, with the aim of understanding the role each plays in modulating the urban microclimate. Methodology – Simulations were performed using ENVI-met software for three scenarios: the current state of the site, the implementation of a planned building, and the inclusion of a green park. Relative humidity was analyzed over a 24-hour period on April 18, 2022. Originality/Relevance – The study highlights relative humidity as a key microclimatic indicator, contributing to discussions on the impact of urban vegetation on environmental quality in cities. Results – The green park scenario had higher humidity levels during the hottest hours of the day, while the densely developed scenario had the lowest levels, especially at night. Theoretical/Methodological Contributions – Reinforces the use of ENVI-met as an effective tool for microclimatic simulations applied to sustainable urban planning. Social and Environmental Contributions – The results highlight the role of green spaces in promoting environmental comfort and supporting public policies aimed at improving urban spaces.